Agroforestry Practices and Community Resilience to The Impact of Climate Change in Sesaot Forest Area, Lombok, Indonesia - Markum Markum; Taslim Sjah; Muhamad Husni Idris; Irwan Mahakam Lesmono Aji; Muhamad Yul Fikry; Firman Ali Rahman (Postgraduate, University of Mataram, 2025)
Climate change affects agroforestry production and community resilience in forest areas. This study aims to: (1) identify vulnerabilities of forest products to climate change; (2) analyze community adaptation strategies; and (3) assess resilience levels of forest-adjacent communities. The research applied descriptive methods via field observations, interviews, and focus group discussions. From 74 residents, random sampling was used (Slovin method, 10% margin of error). Variables included economic, psychological, and social-institutional aspects. Resilience was assessed using a scoring system integrating Reivich & Shatté’s theory and a Likert scale, categorized into five levels: very high to very low. Results show that key vulnerabilities in the Sesaot forest area include harvest failures of major crops (e.g., durian, mangosteen, avocado, rambutan, cacao, coffee), with losses reaching 60–80%. Communities adapted through stratified agroforestry systems and strengthening local institutions. Resilience levels were high overall—economically moderate, but socially and psychologically strong. The study recommends improving economic resilience by reducing crop failure risks, including through the establishment of plant health clinics